2017
DOI: 10.4236/ojepi.2017.71003
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Preoperative Parental Anxiety and Emergence Agitation in Preschoolers

Abstract: Introduction: The preoperative distress and anxiety experienced by preschoolers are associated with an increased incidence of troubled recovery from anesthesia. However, influences of parental anxiety on children at different stages of the surgical processes are not clear. The aim of this study was to evaluate any existing association between preoperative parental anxiety and emergence agitation in a pediatric surgery population. Materials and Methods: A total of 60 children ASA class I or II, aged 3 -12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Moreover, it seems that the gender of the children also influences the anxiety in parents during the postoperative period: the mothers of girls were more anxious than the parents of boys. Similar gender-reliant patterns, but during the preoperative period, were observed by Charana et al [ 28 ] and Erkılıc et al [ 37 ]. Women’s greater vulnerability to anxiety can be partly rationalised by genetic factors, hormonal influences and sociocultural influences [ 38 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, it seems that the gender of the children also influences the anxiety in parents during the postoperative period: the mothers of girls were more anxious than the parents of boys. Similar gender-reliant patterns, but during the preoperative period, were observed by Charana et al [ 28 ] and Erkılıc et al [ 37 ]. Women’s greater vulnerability to anxiety can be partly rationalised by genetic factors, hormonal influences and sociocultural influences [ 38 ].…”
Section: Discussionsupporting
confidence: 83%
“…This is in contrast with reported levels of anxiety in non‐acute setting 17–20 . These include parents of a child who underwent elective surgery 17 , 18 and parents of a child seen in the cardiology clinic for heart murmurs 19 …”
Section: Discussionmentioning
confidence: 90%
“…Save‐Pédebos et al 15 reported higher mean state anxiety score among parents with a child who had the first episode of seizure, 58.7; while parents with febrile children had lower state anxiety score, 50.1 16 . This is in contrast with reported levels of anxiety in non‐acute setting 17–20 . These include parents of a child who underwent elective surgery 17 , 18 and parents of a child seen in the cardiology clinic for heart murmurs 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only pain, but also anxiety is a common problem postoperatively as patients/parents report high levels of anxiety prior to and after tonsillectomy ( Erkılıc et al., 2016 ). The result in Yang et al., (2016) , where the children in the group that received text messages were less anxious than those in the control group, is supported by a study where they conducted a quality improvement project to develop a text messaging service to deliver messages to paediatric tonsillectomy patients to improve communication and overall experience Newton and Sulman (2016) .…”
Section: Discussionmentioning
confidence: 99%